2013
DOI: 10.1016/j.ijcard.2013.03.015
|View full text |Cite
|
Sign up to set email alerts
|

High concentration of C-type natriuretic peptide promotes VEGF-dependent vasculogenesis in the remodeled region of infarcted swine heart with preserved left ventricular ejection fraction

Abstract: CNP expression is locally increased in infarct remodeled myocardium in the presence of dense capillary network. The vasculogenic response requires the co-exposure to high concentration of CNP and VEGF-A. Our data will be helpful to develop combined myocardial delivery of CNP and VEGF-A genes in order to reverse the remodeling process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 48 publications
(50 reference statements)
0
12
0
Order By: Relevance
“…A study with infarcted swine hearts with a preserved EF showed that increased fibrosis, metalloproteases, and capillary density were localized to the infarct border zone and were associated with increased expression of CNP. Interestingly, high concentrations of both CNP and VEGF‐A were associated with a vasculogenic response …”
Section: Discussionmentioning
confidence: 99%
“…A study with infarcted swine hearts with a preserved EF showed that increased fibrosis, metalloproteases, and capillary density were localized to the infarct border zone and were associated with increased expression of CNP. Interestingly, high concentrations of both CNP and VEGF‐A were associated with a vasculogenic response …”
Section: Discussionmentioning
confidence: 99%
“…ANP via NPR-A stimulates endothelial precursor cell proliferation, migration, and differentiation in the skin during cutaneous wound healing 35 . The restoration of blood flow is impaired after hindlimb ischemia in NPR-A KO mice 36 , while the injection of a high concentration of CNP increases vascular density in infarcted swine hearts 37 . Recently, CNP was identified as a key regulator in angiogenesis and vascular remodelling after ischemia in patients suffering from peripheral artery disease 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was extracted by acid guanidinium thiocyanate-phenol-chloroform method from cardiac tissue samples with Rneasy Midi kit (Qiagen S.p.A, Milano, Italy) as previously describe [ 28 30 ]. The extraction methodology used was specific for fibrous tissues, as cardiac samples, and during extraction phases cellular debris were removed.…”
Section: Methodsmentioning
confidence: 99%
“…The cDNA samples obtained were placed on ice and stored at 4°C until further use. Real-Time PCR reactions were performed in duplicate in the Bio-Rad C1000 TM thermal cycler (CFX-96 Real-Time PCR detection systems, Bio-Rad) as previously described [ 30 ]. For monitoring cDNA amplification a third-generation fluorophore, EvaGreen, was used (SsoFAST EvaGreen Supermix, Bio-Rad).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation